Implementation of Nationalism Values in Learning the History of Independence Organizations in Class XI IPS 1 SMA Nasional Nusaputera Semarang - Kasih, Amalia Sekar; Romadi, Romadi; Atno, Atno (Indonesian Journal of History Education, 2020)
The purpose of this study is: (1) How is the implementation of the values of nationalism in the study of history on the subject of independent organizations in a class of XI IPS I in Nusaputera National High School of Semarang? (2) What constraints are experienced by teachers when applying the values of nationalism in the process of learning the history of the subject of independence organizations in class XI IPS I in Nusaputera National High School of Semarang? (3) What efforts are made by teachers to overcome obstacles when applying the values of nationalism in the process of learning the history of the subject of independence organization in class XI IPS I in Nusaputera National High School of Semarang? This research is a descriptive qualitative research. The results showed that the implementation of the value of nationalism in learning history on the subject of independence organizations in the class XI IPS I National Senior High School Nusaputera Semarang has been running well. The value of nationalism implemented was from planning, execution, and evaluation, including religion, pride to be Indonesian, love of homeland and nation, discipline, and appreciation of the service of former heroes. Obstacles experienced by teachers are learning, moral decline, electronic media, and time constraints. Efforts made by teachers are continuously giving the delivery of the value of nationalism